Peningkatan Kesadaran Hukum Masyarakat: Memahami Perbedaan Tindak Pidana Penipuan dan Penggelapan - Ridwan Lubis, Muhammad; Siregar, Gomgom TP; Nurita, Cut; Fraya Hartin Nst, Venny; Lubis, Diana (Bulletin of Community Engagement, 2023)
Embezzlement is the act of dishonestly hiding someone else's property without the owner's knowledge with the intention of transferring ownership, control or use for other purposes. This is considered a type of financial fraud and a violation of criminal law. The crime of fraud is broader than inclusion. Although embezzlement is limited to goods or money, fraud also includes granting debts or writing off receivables. Fraud and embezzlement are considered relative offenses and can be revoked. However, the case will continue to be examined at the investigation, prosecution and trial stages, even though compensation has been paid. Relative offenses are considered ordinary offenses related to the family. If the victim does not file a complaint, then the violation becomes a complaint offense and can only be prosecuted by complaint. Distinguishing between criminal acts of fraud and embezzlement can be determined by the elements of each. An act can be considered fraudulent if it meets the criteria as intended in Article 378 which contains elements of fraud. Conversely, fraud may involve debt or write-offs of receivables. This element is often carried out through repeated seduction or promises to deceive the victim. Fraud has a wider scope than participation which is limited to goods or money in accordance with Article 372 KUPIdana. Any individual or community making purchases must follow the correct payment methods and comply with legal guidelines. Keywords: Public Legal Awareness, Crimes of Fraud, Crime Embezzlement